Management of amputated digits. (2nd November 2020) - Welman, T; Popova, D; Vamadeva, SV; Pahal, GS
Abstract : Traumatic digit amputations account for 1% of all trauma admissions and are an important cause of morbidity in young, working people. It is essential that patients are worked up appropriately and referred promptly to a specialist unit for consideration of replantation. This review summarises the acute management of a patient presenting to the emergency department with an amputated digit. It discusses the assessment, initial management in the emergency department, how to make the decision to replant and operative steps.